(untitled) (JURNAL GEOCELEBES, 2022)
Outcrops of supergene copper mineralization of azurite, and malasite types were found in the Tonra Region, Bone Regency, South Sulawesi Province. Hydrothermal alteration can be used to interpret and understand the origin of supergene mineralization and identify hypogene mineralization. This research includes identification of hydrothermal alteration mineral types and their alteration types. Sample processing using megascopic analysis, microscopic petrography and XRD mineralogy. The results of megascopic analysis show three altered outcrops with physical changes as markers of altered rock. Microscopic analysis of petrography and XRD mineralogy showed the presence of quartz, paligorskit, kaolinite, illite, chlorite, ankerite, calcite, zeolite, epidote, and sphalerite minerals. This research explains that in the research location has two types of argillic and propylitic alteration. The type of argillic alteration is characterized by the presence of quartz-kaolinite-illite minerals, based on the formation temperature in the range of 100-300oC and acidic pH. The propylitic alteration type is characterized by chlorite-epidote-carbonate minerals, based on the formation temperature ranging from 150-300oC and neutral pH.